First-principles calculations to investigate optical properties of B yAl xIn 1-x-yN alloys for optoelectronic devices - Yarub, Al - Douri; Merabet, B.; Abid, H.; Khenata, R. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/